Mg-doped sodium vanadium phosphate, Mg-doped sodium vanadium fluorophosphate, preparation method and use thereof
By doping mg elements and use static spinning method to prepare sodium mixed sodium mos and sodium mixed with mg, sodium sodium sodium, solve the problem of poor sodium sodium sodium material performance, realize the improvement of material multi -rate performance and simplification of technology. Suitable for industrial production.
Patent Information
- Application Number
- CN202211592967.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-13
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2042-12-13
AI Technical Summary
The charge and discharge rate performance of traditional vanadium sodium phosphate materials is poor, and the preparation method is immature, resulting in insufficient rate performance of the material.
By doping the metal Mg element and using electrospinning method to prepare Mg-doped sodium vanadium phosphate and Mg-doped sodium vanadium phosphate, the rate performance of the material can be improved. The method includes dissolving a phosphorus source, a vanadium source and a magnesium source in an organic solvent, forming a fibrous precursor through electrospinning, then mixing it with a sodium source for sand grinding and spray drying, and finally performing high temperature treatment to obtain Mg-doped vanadium phosphate. Sodium or Mg-doped sodium vanadium fluorophosphate.
Improved the multiplier performance of sodium sodium sodium pyrotein material, the larger surface area of sodium sodium phosphate and sodium doped mg, and the lithium ion spread faster. Simple and low equipment price, suitable for industrial production.
Smart Images

Figure CN115818611B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to positive electrode material technology, and in particular to Mg-doped sodium vanadium phosphate, Mg-doped sodium vanadium fluorophosphate, and preparation methods and uses thereof. Background Art
[0002] Among the positive electrode materials for sodium ion batteries, layered transition metal oxides and polyanionic compounds have better performance. Polyanionic compounds with sodium superion conductor (NASICON) structure have attracted much attention because of their open skeleton structure, rapid conduction of sodium ions, and very stable structure during the sodium ion deintercalation process. Sodium vanadium phosphate [Na3V2(PO4)3, abbreviated as NVP] has a typical NASICON structure and a theoretical specific capacity of 117.6 mAh / g. It has Na + It has good ionic conductivity, small volume change during the embedding / de-embedding process, moderate voltage platform (3.4V), high theoretical specific energy (400Wh / kg), and good thermal stability, making it a promising cathode material for sodium ion batteries. However, like other polyanionic compounds, its intrinsic electronic conductivity is low, and the immature preparation method leads to poor rate performance of the material.
[0003] Ion doping is an effective means to improve the rate performance of sodium vanadium phosphate materials. At present, the doping of metal ions in sodium vanadium phosphate materials is mainly based on solid-phase ball milling and sol-gel methods. In the solid-phase ball milling method, sodium source, vanadium source, phosphorus source and doped metal ions are first added to the ball mill according to the stoichiometric ratio, and ethanol is used as a solvent for wet high-speed ball milling. After ball milling, the sample is dried and finally sintered at high temperature under an inert atmosphere to obtain a Na3V2(PO4) sample doped with metal ions. The particles synthesized by this solid-phase method have irregular shapes, which are not conducive to large current charging and discharging; high-speed ball milling consumes a lot of energy, and the synthesis cost increases during large-scale production; in order to ensure the reduction of high-priced vanadium, a reducing agent must be added, which increases the cost of auxiliary materials. The sol-gel method first dissolves the soluble sodium source, vanadium source, phosphorus source and doped metal ions in deionized water, adds citric acid water under medium temperature water bath conditions, adds ammonia water under high temperature water bath conditions to adjust the pH, and then reacts to obtain a precursor gel. Finally, the precursor gel is dried, ground, pre-burned and sintered at high temperature to obtain a Na3V2(PO4) sample doped with metal ions. This sol-gel method has a cumbersome process flow and complex mass production procedures; poor operability and low product consistency; the product produced has low conductivity and fast decay of high current charge and discharge capacity. Summary of the invention
[0004] The purpose of the present invention is to propose a preparation method of Mg-doped sodium vanadium phosphate to address the problem of poor charge and discharge rate performance of traditional sodium vanadium phosphate. The method effectively improves the rate performance of the sodium vanadium phosphate material by doping with metallic Mg element.
[0005] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing Mg-doped sodium vanadium phosphate, comprising the following steps:
[0006] Step 1: dissolving a phosphorus source, a vanadium source and a magnesium source in an organic solvent to prepare a spinning mother solution;
[0007] Step 2: Spraying the spinning solution into a fibrous precursor by electrospinning;
[0008] Step 3: mixing the fibrous precursor with a sodium source, sand milling, and spray drying;
[0009] Step 4: collecting the material obtained after spray drying and subjecting it to high temperature treatment to obtain Mg-doped sodium vanadium phosphate.
[0010] Furthermore, the phosphorus source in step 1 is one or more of sodium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate and ammonium phosphate.
[0011] Furthermore, the vanadium source in step 1 is one or more of vanadium pentoxide, ammonium metavanadate, vanadyl oxalate, ammonium polyvanadate, vanadium dioxide and vanadium trioxide.
[0012] Furthermore, the magnesium source in step 1 is magnesium nitrate and / or magnesium sulfate.
[0013] Furthermore, the organic solvent in step 1 is a mixture of N,N-dimethylformamide (DMF) and polyvinylpyrrolidone (PVP), the mass ratio of N,N-dimethylformamide to polyvinylpyrrolidone is 1:0.05-0.15, and the preferred mass ratio is 1:0.08-0.12.
[0014] Furthermore, the element molar ratio of the phosphorus source, vanadium source and magnesium source in step 1 is 1:0.55-0.8:0.01-0.05, and the mass ratio of the total amount of the phosphorus source, vanadium source and magnesium source to the solvent is 1:3-4; preferably, the element molar ratio of the phosphorus source, vanadium source and magnesium source is 1:0.6-0.7:0.02-0.04, and more preferably, the mass ratio of the total amount of the phosphorus source, vanadium source and magnesium source to the solvent is 1:3.2-3.8.
[0015] Furthermore, the electrospinning in step 2 is oblique-jet electrospinning.
[0016] Furthermore, the electrospinning conditions in step 2 are as follows: voltage 10-12 kV, receiving distance 8-10 cm, relative humidity 20-30%, and ambient temperature 20-24°C.
[0017] Furthermore, the fiber precursor in step 2 needs to be treated at high temperature, the treatment temperature is 400-600°C, and the treatment time is 2-5 hours; the preferred treatment temperature is 450-550°C, and the treatment time is 3-4 hours. The high temperature treatment causes the organic matter in the original fiber to generate CO2 and H2O at high temperature and discharge them.
[0018] Furthermore, the diameter of the fibrous precursor in step 2 is 0.5 to 2 microns.
[0019] Furthermore, the molar ratio of vanadium to sodium in the fibrous precursor of step 3 is 1:0.9-1.1, preferably 1:0.97-1.08, and more preferably 1:1.05.
[0020] Furthermore, the sodium source in step 3 is sodium carbonate and / or sodium hydroxide.
[0021] Further, the sand milling and spray drying conditions in step 3 are as follows: the sand milling feed pump frequency is 2 to 10 s / time, the sand milling speed is 600 to 1400 rpm, the number of cycles is 3 to 10 times, the spray air inlet temperature is 160 to 340 ° C, the atomizing disk speed is 100 to 300 Hz, and the peristaltic pump speed is 30 to 80 rpm. Preferably, the sand milling feed pump frequency is 4 to 6 s / time, and the most preferred sand milling feed pump frequency is 5 s / time; preferably, the sand milling speed is 800 to 1200 rpm, and the most preferred sand milling speed is 1000 rpm; preferably, the number of cycles is 5 to 7 times, and the most preferred number of cycles is 6 times; preferably, the spray air inlet temperature is 190 to 300 ° C, and the most preferred spray air inlet temperature is 240 ° C; preferably, the atomizing disk speed is 150 to 250 Hz, and the most preferred atomizing disk speed is 200 Hz; preferably, the peristaltic pump speed is 40 to 60 rpm, and the most preferred peristaltic pump speed is 50 rpm.
[0022] Furthermore, the high temperature treatment temperature in step 4 is 600-1000°C, and the time is 2-8h; the preferred high temperature treatment temperature is 800-900°C, and the time is 2.5-5.5h; the most preferred high temperature treatment temperature is 850°C, and the time is 3h.
[0023] Another object of the present invention is to disclose a Mg-doped sodium vanadium phosphate prepared by the above-mentioned preparation method of Mg-doped sodium vanadium phosphate.
[0024] Furthermore, the Mg-doped sodium vanadium phosphate is spherical, with a particle size of 5 to 50 microns, preferably a particle size of 10 to 35 microns.
[0025] Another object of the present invention is to disclose the use of Mg-doped sodium vanadium phosphate as a positive electrode material for sodium ion batteries.
[0026] Another object of the present invention is to disclose a positive electrode material, comprising the Mg-doped sodium vanadium phosphate.
[0027] Furthermore, the positive electrode material includes Mg-doped sodium vanadium phosphate, conductive carbon black and polyvinylidene fluoride.
[0028] Furthermore, the positive electrode material includes Mg-doped sodium vanadium phosphate, conductive carbon black and polyvinylidene fluoride in a mass ratio of 8:0.5 to 2:0.8 to 1.2.
[0029] Another object of the present invention is to disclose a method for preparing Mg-doped sodium vanadium fluorophosphate, comprising the following steps:
[0030] Step a: dissolving a phosphorus source, a vanadium source, a fluorine source and a magnesium source in an organic solvent to prepare a spinning mother solution;
[0031] Step b: spraying the spinning solution into a fibrous precursor by electrospinning;
[0032] Step c: mixing the fibrous precursor with a sodium source, sand milling, and spray drying;
[0033] Step d: collecting the spray-dried material and subjecting it to high-temperature treatment to obtain Mg-doped sodium vanadium fluorophosphate.
[0034] Furthermore, the phosphorus source in step a is one or more of sodium phosphate, diammonium phosphate, diammonium hydrogen phosphate and ammonium phosphate.
[0035] Furthermore, the vanadium source in step a is one or more of vanadium pentoxide, ammonium metavanadate, vanadyl oxalate, ammonium polyvanadate, vanadium dioxide and vanadium trioxide.
[0036] Furthermore, the magnesium source in step a is magnesium nitrate and / or magnesium sulfate.
[0037] Furthermore, the fluorine source in step a is one or more of sodium vanadium fluorophosphate, ammonium fluoride, hydrogen fluoride and sodium fluoride.
[0038] Furthermore, the organic solvent in step a is a mixture of N,N-dimethylformamide DMF and / or polyvinylpyrrolidone PVP.
[0039] Furthermore, the element molar ratio of the phosphorus source, vanadium source, magnesium source and fluorine source in step a is 1: 0.95-1.05: 0.01-0.05: 1.4-1.6, and the mass ratio of the total amount of the phosphorus source, vanadium source, magnesium source and fluorine source to the solvent is 1: 3-4; preferably, the element molar ratio of the phosphorus source, vanadium source, magnesium source and fluorine source is 1: 0.98-1.02: 0.02-0.04: 1.45-1.55, and more preferably, the mass ratio of the total amount of the phosphorus source, vanadium source, magnesium source and fluorine source to the solvent is 1: 3.2-3.8.
[0040] Furthermore, the electrospinning in step b is oblique-jet electrospinning.
[0041] Furthermore, the electrospinning conditions in step b are as follows: voltage 10-12 kV, receiving distance 8-10 cm, relative humidity 20-30%, and ambient temperature 20-24°C.
[0042] Furthermore, the fiber precursor in step b needs to be treated at high temperature, the treatment temperature is 400-600° C., and the treatment time is 2-5 hours.
[0043] Furthermore, the diameter of the fibrous precursor in step b is between 0.5 and 2 microns.
[0044] Furthermore, the ratio of vanadium to sodium in the fibrous precursor in step c is 1:1.4-1.6, preferably the molar ratio is 1:1.45-1.55, and more preferably the molar ratio is 1:1.5.
[0045] Furthermore, the sodium source in step c is sodium carbonate and / or sodium hydroxide.
[0046] Further, the sand milling and spray drying conditions in step c are as follows: the sand milling feed pump frequency is 2 to 10 s / time, the sand milling speed is 600 to 1400 rpm, the number of cycles is 3 to 10 times, the spray air inlet temperature is 160 to 340°C, the atomizing disk speed is 100 to 300 Hz, and the peristaltic pump speed is 30 to 80 rpm. Preferably, the sand milling feed pump frequency is 4 to 6 s / time, and the most preferred sand milling feed pump frequency is 5 s / time; preferably, the sand milling speed is 800 to 1200 rpm, and the most preferred sand milling speed is 1000 rpm; preferably, the number of cycles is 5 to 7 times, and the most preferred number of cycles is 6 times; the spray air inlet temperature is 190 to 300°C, and the most preferred spray air inlet temperature is 240°C; preferably, the atomizing disk speed is 150 to 250 Hz, and the most preferred atomizing disk speed is 200 Hz; preferably, the peristaltic pump speed is 40 to 60 rpm, and the most preferred peristaltic pump speed is 50 rpm.
[0047] Furthermore, the high temperature treatment temperature in step d is 600-1000°C for 2-8h; the preferred high temperature treatment temperature is 800-900°C for 2.5-5.5h, and the most preferred high temperature treatment temperature is 850°C for 3h.
[0048] Another object of the present invention is to disclose a Mg-doped sodium vanadium fluorophosphate prepared by the above-mentioned preparation method of Mg-doped sodium vanadium fluorophosphate.
[0049] Furthermore, the Mg-doped sodium vanadium fluorophosphate is spherical, with a particle size of 5 to 50 microns, preferably a particle size of 10 to 35 microns.
[0050] Another object of the present invention is to disclose the use of Mg-doped sodium vanadium fluorophosphate as a positive electrode material for sodium ion batteries.
[0051] Another object of the present invention is to disclose a positive electrode material, comprising the Mg-doped sodium vanadium fluorophosphate.
[0052] Furthermore, the positive electrode material includes Mg-doped sodium vanadium fluorophosphate, conductive carbon black and polyvinylidene fluoride.
[0053] Furthermore, the positive electrode material includes Mg-doped sodium vanadium fluorophosphate, conductive carbon black and polyvinylidene fluoride in a mass ratio of 7 to 9: 0.2 to 2: 0.1 to 1.2.
[0054] The Mg-doped sodium vanadium phosphate, Mg-doped sodium vanadium fluorophosphate, preparation method and use thereof of the present invention have the following advantages compared with the prior art:
[0055] 1) The present invention uses an electrospinning method to prepare a precursor. This method has a simple preparation device, low spinning cost, and strong process controllability; the organic solvent used in electrospinning can dissolve most metal salts and make the doping material more evenly dispersed during the spinning process; the fiber prepared by electrospinning has good consistency and high porosity, which is conducive to sufficient mixing with the sodium source.
[0056] 2) The microspheres of the Mg-doped sodium vanadium phosphate and the Mg-doped sodium vanadium phosphate fluorophosphate have a larger specific surface area than the conventional sodium vanadium phosphate and sodium vanadium phosphate fluorophosphate particles. The specific surface area of the Mg-doped sodium vanadium phosphate and the Mg-doped sodium vanadium phosphate fluorophosphate can be as high as 318 m 2 / kg, which makes lithium ions diffuse faster and improves the rate performance of the positive electrode material. The charging capacity of Mg-doped sodium vanadium phosphate can reach 102mAh / g at 5C current, and the charging capacity of Mg-doped sodium vanadium phosphate can reach 113mAh / g at 5C current.
[0057] 3) The particle size of the Mg-doped sodium vanadium phosphate and the Mg-doped sodium vanadium phosphate is 10 to 35 microns, with uniform distribution, good consistency and good product batch quality.
[0058] 4) The preparation process of the present invention is simple, the equipment is low-cost, no toxic or harmful substances are released, and it is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 This is the XRD diagram of Mg-doped sodium vanadium phosphate in Example 1;
[0060] Figure 2 This is the SEM image of Mg-doped sodium vanadium phosphate in Example 1;
[0061] Figure 3 This is the rate performance curve of Mg-doped sodium vanadium phosphate in Example 1.
[0062] Figure 4 This is the XRD diagram of Mg-doped sodium vanadium phosphate in Example 2;
[0063] Figure 5 This is the SEM image of Mg-doped sodium vanadium phosphate in Example 2;
[0064] Figure 6 This is a rate performance curve diagram of Mg-doped sodium vanadium phosphate in Example 2;
[0065] Figure 7 This is the XRD pattern of Mg-doped sodium vanadium fluorophosphate of Example 3;
[0066] Figure 8 This is the SEM image of Mg-doped sodium vanadium fluorophosphate of Example 3;
[0067] Fig. 9 This is a rate performance curve diagram of Mg-doped sodium vanadium fluorophosphate according to Example 3;
[0068] Fig.10 This is the XRD pattern of Mg-doped sodium vanadium fluorophosphate of Example 4;
[0069] Fig.11 This is the SEM image of Mg-doped sodium vanadium fluorophosphate of Example 4;
[0070] Fig.12 This is a rate performance curve diagram of Mg-doped sodium vanadium fluorophosphate according to Example 4;
[0071] Fig.13 The XRD pattern of Mg-doped sodium vanadium phosphate in control example 1;
[0072] Fig.14 This is the SEM image of Mg-doped sodium vanadium phosphate in control example 1;
[0073] Fig.15 The rate performance curve of Mg-doped sodium vanadium phosphate of control example 1;
[0074] Fig.16 This is the XRD pattern of Mg-doped sodium vanadium fluorophosphate of control example 2;
[0075] Fig.17 This is the SEM image of Mg-doped sodium vanadium fluorophosphate of control example 2;
[0076] Fig.18 The rate performance curve of Mg-doped sodium vanadium fluorophosphate of control example 2; DETAILED DESCRIPTION
[0077] The present invention is further described below in conjunction with embodiments:
[0078] Example 1
[0079] This embodiment discloses a Mg-doped sodium vanadium phosphate, the preparation method of which is as follows:
[0080] Step 1, preparation of spinning solution: according to the molar ratio of phosphorus source, vanadium source and magnesium source of 1:0.65:0.02, sodium phosphate ammonium phosphate, vanadium pentoxide and magnesium nitrate are weighed, and a total of 4.2g of sodium phosphate ammonium phosphate, vanadium pentoxide and magnesium nitrate are added to a mixed organic solvent of N,N-dimethylformamide and polyvinyl pyrrolidone, and stirred continuously until all are dissolved to form a transparent spinning precursor solution. The mixed organic solvent includes 30ml of N,N-dimethylformamide DMF and 3.2g of polyvinyl pyrrolidone PVP.
[0081] Step 2, preparation of fibrous precursor: For the synthesis of original fibers, an oblique jet electrostatic spinning method is used. The high voltage power supply, spinning solution and receiving net form a closed loop through the high voltage generated by the power supply, and then adjust the voltage of the power supply and the distance from the nozzle to the receiving net until continuous fibers are ejected. The spinning conditions are: voltage 12kV, receiving distance 10cm, relative humidity 30%, ambient temperature 24°C. The spun original fibers are placed in a programmable high-temperature box furnace, heated to 500°C at a heating rate of 1°C / min in an air environment, the insulation time is 3h, the cooling rate is 1°C / min, and the temperature naturally drops to room temperature when it reaches 200°C, and the product is a fibrous precursor.
[0082] Step 3, adding sodium source: the obtained fibrous precursor and sodium carbonate were uniformly mixed in a molar ratio of 1:1.05, and then sand-milled. The sand-milling feed pump frequency was 5s / time, the sand-milling speed was 800rpm, and spray-dried after 3 cycles.
[0083] Step 4: Collect the spray-dried material for high-temperature treatment, calcine at 850° C. in a tubular furnace for 3 hours, and obtain spherical (after electrospinning, before adding the sodium source, it is fibrous, after sand milling and spraying, it is spherical, and the final product is spherical) sodium vanadium phosphate active material after natural cooling.
[0084] Figure 1 is the XRD pattern of Mg-doped sodium vanadium phosphate, which shows that the Mg-doped sodium vanadium phosphate prepared in this embodiment is a single phase without other impurities; Figure 2 This is the SEM image of the Mg-doped sodium vanadium phosphate in Example 1. It can be seen that the particles of the Mg-doped sodium vanadium phosphate are uniform, with a primary particle size of about 8 to 28 microns and an average specific surface area of 334 m 2 / kg.
[0085] Preparation of positive electrode material: Mix Mg-doped sodium vanadium phosphate, conductive carbon black Super P and polyvinylidene fluoride PVDF in a mass ratio of 8:1:1, a total of 0.3 g, in 120 mml of N-methylpyrrolidone NMP, and evenly coat and press to make positive electrode material. Figure 3As shown, a sodium ion button battery was assembled with a sodium sheet as the counter electrode, and charge and discharge tests were carried out at a voltage of 2.5-3.8V. The first charge capacity at a rate of 0.2C was 117.3mAh / g, and the discharge capacity was 112.6mAh / g. The charge capacity at a rate of 5C was 105.7mAh / g, and the discharge capacity was 103.5mAh / g.
[0086] Example 2
[0087] This embodiment discloses a Mg-doped sodium vanadium phosphate, the preparation method of which is as follows:
[0088] Step 1, preparation of spinning solution: according to the molar ratio of phosphorus source, vanadium source and magnesium source of 1:0.67:0.03, ammonium dihydrogen phosphate, ammonium metavanadate and magnesium sulfate are weighed, and 5.1g of ammonium dihydrogen phosphate, ammonium metavanadate and magnesium sulfate are added to a mixed organic solvent of N, N-dimethylformamide and polyvinyl pyrrolidone, and stirred continuously until all are dissolved to form a transparent spinning precursor solution. The mixed organic solvent includes 35ml of N, N-dimethylformamide DMF and 4.4g of polyvinyl pyrrolidone PVP.
[0089] Step 2, preparation of fibrous precursor: For the synthesis of original fibers, an oblique jet electrostatic spinning method is used. The high voltage power supply, spinning solution and receiving net form a closed loop through the high voltage generated by the power supply, and then adjust the voltage of the power supply and the distance from the nozzle to the receiving net until continuous fibers are ejected. The spinning conditions are: voltage 10kV, receiving distance 8cm, relative humidity 28%, ambient temperature 26°C, the spun original fiber is placed in a temperature-controlled box furnace, heated to 400°C at a heating rate of 2°C / min in an air environment, the heat preservation time is 4h, the cooling rate is 2°C / min, and the temperature is naturally reduced to room temperature when it reaches 150°C, and the product is a fibrous precursor.
[0090] Step 3, adding sodium source: the obtained fibrous precursor and sodium hydroxide were uniformly mixed in a molar ratio of 1:1.03, and then sand milled. The sand milling feed pump frequency was 8s / time, the sand milling speed was 1000rpm, and spray drying was performed after 2 cycles.
[0091] Step 4: Collect the spray-dried material for high-temperature treatment, calcine at 800° C. for 5 h in a tubular furnace, and obtain spherical Mg-doped sodium vanadium phosphate active material after natural cooling.
[0092] Figure 4 is the XRD pattern of Mg-doped sodium vanadium phosphate, which shows that the Mg-doped sodium vanadium phosphate prepared in this embodiment is a single phase without other impurities; Figure 5 This is the SEM image of the Mg-doped sodium vanadium phosphate in Example 1. It can be seen that the particles of the Mg-doped sodium vanadium phosphate are uniform, with a primary particle size of about 10 to 30 microns and an average specific surface area of 315 m2 / kg.
[0093] Preparation of positive electrode material: Mix Mg-doped sodium vanadium phosphate, conductive carbon black Super P and polyvinylidene fluoride PVDF in a mass ratio of 8:1:1, a total of 0.3 g, in 120 mml of N-methylpyrrolidone NMP, and evenly coat and press to make positive electrode material. Figure 6 As shown, a sodium ion button battery was assembled with a sodium sheet as the counter electrode, and charge and discharge tests were carried out at a voltage of 2.5-3.8V. The first charge capacity at a rate of 0.2C was 116.2mAh / g, and the discharge capacity was 109.4mAh / g. The charge capacity at a rate of 5C was 105.7mAh / g, and the discharge capacity was 102.6mAh / g.
[0094] Example 3
[0095] This embodiment discloses a Mg-doped sodium vanadium fluorophosphate, the preparation method of which is as follows:
[0096] Step 1, preparation of spinning solution: according to the molar ratio of phosphorus source, vanadium source, magnesium source and fluorine source of 1:1:0.03:1.5, diammonium hydrogen phosphate, ammonium polyvanadate, magnesium nitrate and ammonium fluoride are weighed, and a total of 5.5g of diammonium hydrogen phosphate, ammonium polyvanadate, magnesium nitrate and ammonium fluoride are added to a mixed organic solvent of N, N-dimethylformamide and polyvinyl pyrrolidone, and stirred continuously until all are dissolved to form a transparent spinning precursor solution. The mixed organic solvent includes 33ml of N, N-dimethylformamide DMF and 3.4g of polyvinyl pyrrolidone PVP.
[0097] Step 2, preparation of fibrous precursor: For the synthesis of the original fiber, an oblique jet electrostatic spinning method is used. The high voltage power supply, spinning solution and receiving net form a closed loop through the high voltage generated by the power supply, and then adjust the voltage of the power supply and the distance from the nozzle to the receiving net until continuous fibers are ejected. The spinning conditions are: voltage 10kV, receiving distance 10cm, relative humidity 25%, ambient temperature 24℃, the spun original fiber is placed in a temperature-controlled box furnace, heated to 450℃ at a heating rate of 1℃ / min in an air environment, the holding time is 3h, the cooling rate is 1℃ / min, and the temperature naturally drops to room temperature when it reaches 200℃, and the product is a fibrous precursor.
[0098] Step 3, adding sodium source: the obtained fibrous precursor and sodium carbonate were uniformly mixed in a molar ratio of 1:1.04, and then sand-milled. The sand-milling feed pump frequency was 6s / time, the sand-milling speed was 900rpm, and spray-dried after 4 cycles.
[0099] Step 4: Collect the spray-dried material for high-temperature treatment, calcine at 850° C. for 3 h in a tubular furnace, and obtain spherical Mg-doped sodium vanadium fluorophosphate active material after natural cooling.
[0100] Figure 7 Mg-doped sodium vanadium fluorophosphate is an XRD pattern, and it can be seen that the Mg-doped sodium vanadium fluorophosphate prepared in this embodiment is a single phase without other impurities; Figure 8 This is the SEM of Mg-doped sodium vanadium fluorophosphate. It can be seen that the particles of Mg-doped sodium vanadium fluorophosphate are uniform, with a primary particle size of about 10 to 33 microns and an average specific surface area of 374m 2 / kg.
[0101] Preparation of positive electrode material: Mix Mg-doped sodium vanadium fluorophosphate, conductive carbon black Super P and polyvinylidene fluoride PVDF in a mass ratio of 94:4:2, 0.3 g in total, and evenly coat and press into a sheet in 120 mml N-methylpyrrolidone NMP to prepare a positive electrode material. Fig. 9 As shown, a sodium ion button battery was assembled with a sodium sheet as the counter electrode, and charge and discharge tests were carried out between a voltage of 2.5 and 4.5 V. The first charge capacity at a rate of 0.2C was 124.1 mAh / g, and the discharge capacity was 117.2 mAh / g. The charge capacity at a rate of 5C was 115.8 mAh / g, and the discharge capacity was 114.2 mAh / g.
[0102] Example 4
[0103] This embodiment discloses a Mg-doped sodium vanadium fluorophosphate, the preparation method of which is as follows:
[0104] Step 1, preparation of spinning solution: according to the molar ratio of phosphorus source, vanadium source, magnesium source and fluorine source of 1:1.02:0.05:1.55, 6g of ammonium phosphate, vanadium trioxide, magnesium sulfate and hydrogen fluoride are weighed, added into 35ml of dimethylformamide DMF, and stirred continuously until all dissolved, then 4g of polyvinylpyrrolidone PVP is added and stirred continuously until a transparent spinning precursor solution is formed.
[0105] Step 2, preparation of fibrous precursor: For the synthesis of original fibers, an oblique jet electrostatic spinning method is used. The high voltage power supply, spinning solution and receiving net form a closed loop through the high voltage generated by the power supply, and then adjust the voltage of the power supply and the distance from the nozzle to the receiving net until continuous fibers are ejected. The spinning conditions are: voltage 12kV, receiving distance 8cm, relative humidity 30%, ambient temperature 26℃, the spun original fiber is placed in a temperature-controlled box furnace, heated to 500℃ at a heating rate of 1℃ / min in an air environment, the holding time is 2h, the cooling rate is 1℃ / min, and the temperature naturally drops to room temperature when it reaches 100℃, and the product is a fibrous precursor.
[0106] Step 3, adding sodium source: the obtained fibrous precursor and sodium carbonate were uniformly mixed in a molar ratio of 1:1.03, and then sand-milled. The sand-milling feed pump frequency was 5s / time, the sand-milling speed was 1000rpm, and spray-dried after 5 cycles.
[0107] Step 4: Collect the spray-dried material for high-temperature treatment, calcine at 800° C. for 5 h in a tubular furnace, and obtain spherical Mg-doped sodium vanadium fluorophosphate active material after natural cooling.
[0108] Fig.10 Mg-doped sodium vanadium fluorophosphate is an XRD pattern, and it can be seen that the Mg-doped sodium vanadium fluorophosphate prepared in this embodiment is a single phase without other impurities; Fig.11 This is the SEM of Mg-doped sodium vanadium fluorophosphate. It can be seen that the particles of Mg-doped sodium vanadium fluorophosphate are uniform, with a primary particle size of about 20 to 40 microns and an average specific surface area of 387 m 2 / kg.
[0109] Preparation of positive electrode material: Mix Mg-doped sodium vanadium fluorophosphate, conductive carbon black Super P and polyvinylidene fluoride PVDF in a mass ratio of 94:4:2, 0.3 g in total, and evenly coat and press into a sheet in 120 mml N-methylpyrrolidone NMP to prepare a positive electrode material. Fig.12 As shown, a sodium ion button battery was assembled with a sodium sheet as the counter electrode, and charge and discharge tests were carried out at a voltage of 2.5-4.5V. The first charge capacity at a rate of 0.2C was 123.3mAh / g, and the discharge capacity was 118.8mAh / g. The charge capacity at a rate of 5C was 112.7mAh / g, and the discharge capacity was 111.6mAh / g.
[0110] Comparative Example 1
[0111] This embodiment discloses a sodium vanadium phosphate not doped with Mg, and the preparation method thereof is as follows:
[0112] Step 1, preparation of spinning solution: Weigh 4.8 g of ammonium phosphate and vanadium pentoxide according to the molar ratio of phosphorus source to vanadium source of 1:0.65, add them into 34 ml of dimethylformamide (DMF), continue stirring until completely dissolved, then add 4.1 g of polyvinylpyrrolidone (PVP) and continue stirring until a transparent spinning precursor solution is formed.
[0113] Step 2, preparation of fibrous precursor: For the synthesis of original fibers, an oblique jet electrostatic spinning method is used. The high voltage power supply, spinning solution and receiving net form a closed loop through the high voltage generated by the power supply, and then adjust the voltage of the power supply and the distance from the nozzle to the receiving net until continuous fibers are ejected. The spinning conditions are: voltage 10.5kV, receiving distance 9cm, relative humidity 28%, ambient temperature 25℃, the spun original fiber is placed in a temperature-controlled box furnace, heated to 450℃ at a heating rate of 1℃ / min in an air environment, the holding time is 6h, the cooling rate is 1℃ / min, and the temperature naturally drops to room temperature when it reaches 100℃, and the product is a fibrous precursor.
[0114] Step 3, adding sodium source: the obtained fibrous precursor and sodium hydroxide were uniformly mixed in a molar ratio of 1:1.05, and then sand-milled. The sand-milling feed pump frequency was 5s / time, the sand-milling speed was 800rpm, and spray-dried after 4 cycles.
[0115] Step 4: Collect the spray-dried material for high-temperature treatment, calcine at 850° C. for 2 h in a tubular furnace, and obtain spherical sodium vanadium phosphate active material after natural cooling.
[0116] like Fig.13 XRD spectrum analysis shows that the prepared sodium vanadium phosphate is a single phase without other impurities. Fig.14 The SEM image shows that the particles of sodium vanadium phosphate are uniform, with a primary particle size of about 10 to 30 microns and an average specific surface area of 335 m 2 / kg.
[0117] Preparation of positive electrode material: Sodium vanadium phosphate, conductive carbon black Super P and polyvinylidene fluoride PVDF in a ratio of 8:1:1, 0.3 g in total, are mixed in 120 mml of N-methylpyrrolidone NMP, coated evenly, and pressed into a sheet to prepare a positive electrode material. Fig.15 As shown, a sodium ion button battery was assembled with a sodium sheet as the counter electrode, and charge and discharge tests were carried out at a voltage of 2.5-3.8V. The first charge capacity at a rate of 0.2C was 113.4mAh / g, and the discharge capacity was 108.2mAh / g. The charge capacity at a rate of 5C was 98.2mAh / g, and the discharge capacity was 95.2mAh / g.
[0118] Comparative Example 2
[0119] This embodiment discloses a Mg-free sodium vanadium fluorophosphate, the preparation method of which is as follows:
[0120] Step 1, preparation of spinning solution: according to the molar ratio of phosphorus source, vanadium source and fluorine source of 1:1.02:1.55, 3.5g of diammonium hydrogen phosphate, ammonium metavanadate and ammonium fluoride were weighed, added into 25ml of dimethylformamide DMF, and stirred continuously until all dissolved, and then 2.8g of polyvinyl pyrrolidone PVP was added and stirred continuously until a transparent spinning precursor solution was formed.
[0121] Step 2, preparation of fibrous precursor: For the synthesis of original fibers, an oblique jet electrostatic spinning method is used. The high voltage power supply, spinning solution and receiving net form a closed loop through the high voltage generated by the power supply, and then adjust the voltage of the power supply and the distance from the nozzle to the receiving net until continuous fibers are ejected. The spinning conditions are: voltage 12kV, receiving distance 12cm, relative humidity 25%, ambient temperature 25℃, the spun original fiber is placed in a temperature-controlled box furnace, heated to 500℃ at a heating rate of 1℃ / min in an air environment, the holding time is 2h, the cooling rate is 1℃ / min, and the temperature naturally drops to room temperature when it reaches 180℃, and the product is a fibrous precursor.
[0122] Step 3, adding sodium source: the obtained fibrous precursor and sodium carbonate were uniformly mixed in a molar ratio of 1:1.05, and then sand-milled. The sand-milling feed pump frequency was 5s / time, the sand-milling speed was 700rpm, and spray-dried after 6 cycles.
[0123] Step 4: Collect the spray-dried material for high-temperature treatment, calcine at 900° C. for 3 h in a tubular furnace, and obtain spherical sodium vanadium fluorophosphate active material after natural cooling.
[0124] like Fig.16 XRD spectrum analysis shows that the prepared sodium vanadium fluorophosphate is a single phase without other impurities. Fig.17 The SEM image shows that the particles of sodium vanadium fluorophosphate are uniform, with a primary particle size of about 15 to 35 microns and an average specific surface area of 363 m 2 / kg.
[0125] Preparation of positive electrode material: Sodium vanadium fluorophosphate, conductive carbon black Super P and polyvinylidene fluoride PVDF in a ratio of 94:4:2, 0.3 g in total, are mixed in 120 mml of N-methylpyrrolidone NMP, coated evenly, and pressed into a sheet to prepare a positive electrode material. Fig.18 As shown, a sodium ion button battery was assembled with a sodium sheet as the counter electrode, and charge and discharge tests were carried out between a voltage of 2.5 and 4.5 V. At a rate of 0.2C, the first charge capacity was 120.9 mAh / g, and the discharge capacity was 114.6 mAh / g. At a rate of 5C, the charge capacity was 109.2 mAh / g, and the discharge capacity was 106.7 mAh / g.
[0126] Comparative Example 3
[0127] This embodiment discloses a Mg-doped sodium vanadium phosphate, the preparation method of which is as follows:
[0128] Step 1, preparation of the precursor: first dissolve 51g of vanadium pentoxide and 6g of magnesium sulfate in 266g of secondary water, and mechanically stir in a 95°C water bath until uniform; weigh 145g of industrial phosphoric acid with a concentration of 75%, slowly add it to a beaker, and continue to stir in a 95°C water bath for 1 hour. The reaction continues to form a dark green solution, and then the dark green solution is introduced into a culture dish and placed in a 100°C blast oven for drying before solidification; finally, the dried sample is ground into powder and placed in a tubular furnace for high-temperature calcination. The calcination conditions are calcination at 500°C for 2 hours under argon (200ml / min) protection, and then the temperature is continued to rise to 850°C and calcined for 2 hours to finally obtain a Mg-doped vanadium phosphate precursor.
[0129] Step 2, adding sodium source: the Mg-doped vanadium phosphate precursor and sodium hydroxide were uniformly mixed in a molar ratio of 1:1.03 and then sand-milled. The sand-milling feed pump frequency was 6s / time, the sand-milling speed was 700rpm, and spray-dried after 5 cycles.
[0130] Step 3: Collect the spray-dried material for high-temperature treatment, calcine at 800° C. for 3 h in a tube furnace, and obtain the Mg-doped sodium vanadium phosphate active material after natural cooling.
[0131] XRD spectrum analysis shows that the prepared Mg-doped sodium vanadium phosphate is a single phase without other impurities. The SEM image shows that the particles of Mg-doped sodium vanadium phosphate are uniform, with a primary particle size of about 15 to 30 microns and an average specific surface area of 357 m 2 / kg.
[0132] Preparation of positive electrode material: Sodium vanadium phosphate, conductive carbon black Super P and polyvinylidene fluoride PVDF were mixed in a ratio of 8:1:1, 0.3g in total, and evenly coated and pressed into sheets in 120mml N-methylpyrrolidone NMP to make positive electrode material. Sodium sheets were used as counter electrodes to assemble sodium ion button cells, and charge and discharge tests were carried out at a voltage of 2.5-3.8V. The first charge capacity at a rate of 0.2C was 112.1mAh / g, and the discharge capacity was 107.3mAh / g. The charge capacity at a rate of 5C was 92.2mAh / g, and the discharge capacity was 90.5mAh / g.
[0133] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A Mg-doped sodium vanadium phosphate, characterized in that: The preparation method of Mg-doped sodium vanadium phosphate comprises the following steps: Step 1: dissolving a phosphorus source, a vanadium source and a magnesium source in an organic solvent to prepare a spinning mother solution; Step 2: Spraying the spinning solution into a fibrous precursor by electrospinning; Step 3: mixing the fibrous precursor with a sodium source, sand milling, and spray drying; Step 4: collecting the spray-dried material and subjecting it to high-temperature treatment at a temperature of 800-900° C. for 2.5-5.5 hours to obtain Mg-doped sodium vanadium phosphate; the Mg-doped sodium vanadium phosphate is spherical and has a particle size of 10-35 μm; The phosphorus source in step 1 is one or more of sodium phosphate, diammonium phosphate, diammonium hydrogen phosphate and ammonium phosphate; The vanadium source in step 1 is one or more of vanadium pentoxide, ammonium metavanadate, vanadyl oxalate, ammonium polyvanadate, vanadium dioxide and vanadium trioxide; The magnesium source in step 1 is magnesium nitrate and / or magnesium sulfate; The organic solvent in step 1 is a mixture of N,N-dimethylformamide and polyvinyl pyrrolidone, and the mass ratio of N,N-dimethylformamide to polyvinyl pyrrolidone is 1:0.05-0.
15.
2. The Mg-doped sodium vanadium phosphate according to claim 1, characterized in that: The element molar ratio of the phosphorus source, vanadium source and magnesium source in step 1 is 1:0.55-0.8:0.01-0.05, and the mass ratio of the total amount of the phosphorus source, vanadium source and magnesium source to the solvent is 1:3-4; And / or, the element molar ratio of vanadium to sodium in the fibrous precursor of step 3 is 1:0.9-1.
1.
3. Use of the Mg-doped sodium vanadium phosphate according to claim 1 as a positive electrode material for sodium ion batteries.
4. A Mg-doped sodium vanadium fluorophosphate, characterized in that: The preparation method of Mg-doped sodium vanadium fluorophosphate comprises the following steps: Step a: dissolving a phosphorus source, a vanadium source, a fluorine source and a magnesium source in an organic solvent to prepare a spinning mother solution; Step b: spraying the spinning solution into a fibrous precursor by electrospinning; Step c: mixing the fibrous precursor with a sodium source, sand milling, and spray drying; Step d: collecting the spray-dried material and subjecting it to high-temperature treatment at a temperature of 800-900° C. for 2.5-5.5 hours to obtain Mg-doped sodium vanadium fluorophosphate, which is spherical and has a particle size of 10-35 μm. The phosphorus source in step a is one or more of sodium phosphate, diammonium phosphate, diammonium hydrogen phosphate and ammonium phosphate; The vanadium source in step a is one or more of vanadium pentoxide, ammonium metavanadate, vanadyl oxalate, ammonium polyvanadate, vanadium dioxide and vanadium trioxide; The magnesium source in step a is magnesium nitrate and / or magnesium sulfate; The fluorine source in step a is one or more of sodium vanadium fluorophosphate, ammonium fluoride, hydrogen fluoride and sodium fluoride; The organic solvent in step a is a mixture of N,N-dimethylformamide (DMF) and polyvinylpyrrolidone (PVP).
5. The method for preparing Mg-doped sodium vanadium fluorophosphate according to claim 4, characterized in that: The molar ratio of the phosphorus source, vanadium source, magnesium source and fluorine source in step a is 1:0.95-1.05:0.01-0.05:1.4-1.6, and the mass ratio of the total amount of the phosphorus source, vanadium source, magnesium source and fluorine source to the solvent is 1:3-4; And / or the molar ratio of vanadium to sodium in the fibrous precursor of step c is 1:1.4-1.
6.
6. Use of the Mg-doped sodium vanadium fluorophosphate according to claim 4 as a positive electrode material for sodium ion batteries.
Citation Information
Patent Citations
Method for preparing Na3V2(PO4)3 nanofiber cathode material
CN109950536A
Fibrous sodium vanadium fluorophosphate positive electrode material and preparation method and application thereof
CN111416107A